Short term effect of an empowerment education intervention on substance use among adolescents living in peri-urban communities, Abuja, Nigeria - Shuaibu, Hassana Ojonuba; Abdul Rahman, Haliza; Mohd Zulkefli, Nor Afiah (Universiti Sultan Zainal Abidin, Malaysia., 2022)
Physiological and emotional changes during adolescence increases their vulnerability to the adoption of risky behaviour such as substance use. Hence, adolescence has been reported to be a critical risk period for initiating the use of substances [1]. In Nigeria, research has shown a high prevalence of substance use among adolescents